Pengaruh Jenis Bonggol dan Konsentrasi Ba terhadap Pertumbuhan Vegetatif P pada Tanaman Pisang Kepok Manado - Angga Sukowardana; Kushendarto Kushendarto; Rugayah Rugayah (Jurnal Penelitian Pertanian Terapan, 2015)
This study aimed to (1) determined the effect of BA concentration on the growth of banana seedlings origin hump cleavage. (2) determined the effect of different origin banana weevil seedling growth and tuber production of tillers. (3) determined the effect of BA concentration on the growth of seedlings and saplings of origin hump hump production. This research has been carried out in January 2013 to April 2013 in the Integrated Field Laboratory, University of Lampung, Bandar Lampung. The design of the experiment using a randomized block design with 3 replications were once created as a test group. Grouping is done based on the size of the hump and time of observation. Arranged in a factorial design of treatment (4 x 2) consisting of two factors; The first factor is the concentration of benzyladenine (BA) consists of 4 levels of concentration are: 0, 50, 100, and 150 ppm. The second factor is the hump that comes from plants that have been producing, and tubers of plants are still puppies. The results showed: (1). Use of BA with a concentration of 50, 100 and 150 ppm had no significant effect on all the variables of observation. (2). Type tuber production yield better growth than puppies hump seen from the variable leaf length, root length, leaf width, number of roots, and the girth so it better be made for seedlings compared with seedling tubers. (3) Pemberian BA with various concentrations of either the production or hump hump tillers showed no difference in the growth of shoots. Keywords: nursery, benzyladenine, hump production, hump tillers